The Role of Investment Literacy in Stock Investment Decision Making in the Indonesian Capital Market: A Literature Review - Wahyu Febri Ramadhan Sudirman (General Multidisciplinary Research Journal, 2025)
Introduction: This study aims to analyze the role of investment literacy in stock investment decision-making in the Indonesian capital market. Investment literacy is a crucial factor in shaping rational and long-term investment behavior, especially amidst increasing public participation in capital market instruments. Methods: This study employed a Systematic Literature Review (SLR) with the PRISMA approach. Data was obtained from the Publish or Perish database and Google Scholar, with a total of 174 articles identified from 2021-2022. After a selection and eligibility assessment process, 20 articles that met the criteria were analyzed to identify patterns, themes, and relationships between relevant variables. Results: The results indicate that investment literacy positively influences the quality of investment decision-making. Investors with high levels of literacy are better able to understand risks, conduct rational analysis, and avoid behavioral biases such as overconfidence and herding. Furthermore, demographic factors such as age, education, experience, and gender also strengthen this relationship. Conclusion and Suggestion: The study concludes that improving investment literacy plays a significant role in fostering rational investment behavior in the Indonesian capital market. Efforts to improve financial literacy through education, training, and public outreach are needed. Future research is recommended to include variables such as digital financial literacy, fintech adoption, and Islamic financial literacy to make the results more relevant to modern financial developments.